Excessive exercise habits of runners as new signs of hypertension and arrhythmia. (15th August 2016) - Kim, Young-Joo; Kim, Chul-Hyun; Park, Kyoung-Min
Abstract: Background: Excessive exercise may induce arrhythmia, and this risk is higher in middle-aged people. The study aim was to compare the exercise characteristics of middle-aged runners participating in excessive endurance exercise. Methods: The subjects of this study were 552 runners (mean age; 49.0 ± 7.4 years) without structural heart disease who performed exercise at least twice per week, had consistently exercised for at least three years, and had finished at least five marathons. The arrhythmia runner group (ARG, n = 14) and normal runner group (NRG, n = 538) were compared with regard to hemodynamic response, cardiorespiratory fitness level, training history, number of finished races, finishing times, and exercise habits. Results: The mean resting systolic (134.0 ± 15.8 mm Hg) and diastolic (85.8 ± 10.9 mm Hg) blood pressure values indicated pre-hypertension, while the mean maximal SBP (213.7 ± 27.4 mm Hg) values indicated exercise-induced hypertension. The VO2max was significantly higher and the maximal DBP was significantly lower in the ARG than in the NRG (p < 0.05). Training history was significantly longer in the ARG than in the NRG (p < 0.05), while the number of finished marathons, the finishing times in marathons and the exercise frequency per week didn't differ significantly between the two groups. Exercise intensity was significantly higher in the ARG than in the NRG (p < 0.01). Conclusions: Middle-aged long-distance runners showed pre-hypertension and exercise-induced hypertension, and the ARG had higher VO2max values, greater exercise intensities, and longer training histories than the NRG.